Hypoxia‐Activated Prodrugs of PERK Inhibitors. Issue 8 (29th January 2019) - Liew, Lydia P.; Singleton, Dean C.; Wong, Way W.; Cheng, Gary J.; Jamieson, Stephen M. F.; Hay, Michael P.
Abstract: Tumour hypoxia plays an important role in tumour progression and resistance to therapy. Under hypoxia unfolded proteins accumulate in the endoplasmic reticulum (ER) and this stress is relieved through the protein kinase R‐like ER kinase (PERK) signalling arm of the unfolded protein response (UPR). Targeting the UPR through PERK kinase inhibitors provides tumour growth inhibition, but also elicits on‐mechanism normal tissue toxicity. Hypoxia presents a target for tumour‐selective drug delivery using hypoxia‐activated prodrugs. We designed and prepared hypoxia‐activated prodrugs of modified PERK inhibitors using a 2‐nitroimidazole bioreductive trigger. The new inhibitors retained PERK kinase inhibitory activity and the corresponding prodrugs were strongly deactivated. The prodrugs were able to undergo fragmentation following radiolytic reduction, or bioreduction in HCT116 cells, to release their effectors, albeit inefficiently. We examined the effects of the prodrugs on PERK signalling in hypoxic HCT116 cells. This study has identified a 2‐substituted nitroimidazole carbamate prodrug with potential to deliver PERK inhibitors in a hypoxia‐selective manner. Abstract : This study will perk you up : Tumour hypoxia causes endoplasmic reticulum (ER) stress which is moderated through protein kinase R‐like ER kinase (PERK) mediated signaling. However, hypoxia also presents a tumour‐selective target for prodrug delivery. We designed and prepared hypoxia‐activated prodrugs of PERK inhibitors and evaluated their activity as PERK inhibitors, their hypoxia‐selective activation and their modulation of PERK signalling in cells.